A ceramic-based composite high-temperature absorbing material and its preparation method and application
By introducing multi-layer interfaces and bismuth layered ceramic phases into the ceramic matrix composite material and combining with the ceramic matrix, the problems of poor stability and insufficient mechanical strength of existing high-temperature absorbing materials at high temperatures are solved, and a ceramic matrix composite high-temperature absorbing material that maintains wave absorption and mechanical properties in a high-temperature environment are realized.
Patent Information
- Application Number
- CN202510048909.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing high-temperature electromagnetic wave absorbing materials have poor stability in high-temperature environments, reduced wave absorption performance, and insufficient mechanical strength, which cannot meet the strength and stability requirements in high-temperature environments.
Ceramic matrix composite materials are used, including fiber prefabricated bodies, multi-layer interfaces, bismuth layered structural ceramic phases and ceramic substrates. By depositing PyC, BN and SiC interfaces, and injecting wave absorbing phase slurry and ceramic matrix precursors into the fiber prefabricated bodies. After multiple impregnation and anaerobic thermal cracking treatments, a ceramic matrix composite high-temperature absorbing material with excellent mechanical properties and high temperature stability is formed.
Maintain good wave absorption performance at high temperatures, combines excellent mechanical properties and thermal stability, and is suitable for heat resistance protection, aerospace, radar wave absorption, stealth technology, electronic warfare and communication shielding.
Smart Images

Figure CN119462171B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of composite materials, and in particular relates to a ceramic-based composite high-temperature absorbing material and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern electronic equipment and aerospace technology, the demand for high-temperature electromagnetic wave shielding and absorbing materials is increasing, especially in high temperature and extreme working environments. The existing absorbing materials on the market generally have certain limitations, especially in terms of poor stability in high temperature environments, and long-term exposure to high temperatures will lead to a decrease in absorbing performance. For example, although carbon-based composites and metal-based composites have good absorbing properties at room temperature, they are prone to oxidation, thermal expansion mismatch and other problems at high temperatures, resulting in a significant decline in the absorbing effect. In addition, the mechanical strength of these materials is often low, and they cannot withstand the strength and stability required in high temperature environments, especially in extreme high temperature environments. The thermal stability and corrosion resistance of the materials are often not ideal. Therefore, the development of a composite material that can not only stably absorb waves at high temperatures, but also meet the requirements of high strength and high heat resistance has become the key to solving this problem.
[0003] Fiber-reinforced ceramic matrix composites have been widely used in aerospace, military protection and engineering structures in high temperature environments in recent years due to their excellent high temperature stability, mechanical properties and corrosion resistance. Fibers (such as carbon fibers, silicon carbide fibers, etc.) have high specific strength and specific stiffness, which can provide the load-bearing effect required by composite materials, while the ceramic matrix has good high temperature resistance and thermal stability, and can adapt to extreme working conditions. However, although fiber-reinforced ceramic matrix composites have excellent mechanical properties in high temperature environments, their electromagnetic wave absorption performance may not meet the requirements of high-efficiency absorbing materials. Due to the poor electromagnetic properties of the ceramic matrix and the limited absorption of electromagnetic waves by the fibers themselves, traditional fiber-reinforced ceramic matrix composites are difficult to provide ideal absorbing effects at high temperatures. Therefore, how to improve the electromagnetic wave absorption performance of ceramic matrix composites while maintaining their high temperature stability has become an important topic in current material research. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a ceramic-based composite high-temperature absorbing material and a preparation method and application thereof. The composite material provided by the present invention can maintain good absorbing performance at high temperatures and has excellent mechanical properties and thermal stability.
[0005] The present invention provides a ceramic-based composite high-temperature absorbing material, the components of which include: a fiber preform, a multilayer interface, an absorbing phase and a ceramic matrix;
[0006] The fiber preform is a structural bearing member of the ceramic-based composite high-temperature absorbing material;
[0007] The multilayer interface is deposited on the surface of the fiber preform, including a PyC interface, a BN interface and a SiC interface;
[0008] The absorbing phase is dispersed inside the fiber preform and is a bismuth layered structure ceramic phase, and the specific composition is CaBi2Nb2O9, Bi3TiTaO9, Na 0.5 Bi 4.5 Ti4O 15 or Bi3TiNbO9;
[0009] The ceramic matrix is filled in the interior of the fiber preform and the surface of the multilayer interface, and its composition is one or more of SiC, Si3N4 and SiCN.
[0010] Preferably, the fibers in the fiber preform are one or more of carbon fibers, silica fibers, silicon carbide fibers, glass fibers, alumina fibers and zirconia fibers.
[0011] Preferably, the fiber preform is woven in a manner of 2.5D acupuncture, three-dimensional orthogonal, fine-weave puncture or layer suture, and has a body density of 0.4-0.7 g / cm 3 The fiber volume fraction is 10~50vol% and the thickness is 2~15mm.
[0012] Preferably, the PyC interface is deposited on the surface of the fiber preform, the BN interface is deposited on the surface of the PyC interface, and the SiC interface is deposited on the surface of the BN interface.
[0013] Preferably, the thickness of the PyC interface is 100 nm to 1 μm; the thickness of the BN interface is 100 nm to 1 μm; and the thickness of the SiC interface is 100 nm to 2 μm.
[0014] The present invention provides a method for preparing the ceramic-based composite high-temperature absorbing material of the above technical solution, comprising the following steps:
[0015] a) depositing a PyC interface, a BN interface and a SiC interface on the surface of the fiber preform to obtain a fiber preform having a multi-layer interface deposited thereon;
[0016] b) injecting a slurry of a microwave absorbing phase into the fiber preform on which the multi-layer interface is deposited, and drying and compacting the slurry to obtain a fiber preform with the microwave absorbing phase dispersed therein;
[0017] c) placing the fiber preform with the absorbing phase dispersed therein in a ceramic matrix precursor for impregnation, and after the impregnation is completed, taking out the fiber preform for anaerobic thermal cracking to crack the impregnated ceramic matrix precursor into a ceramic phase, thereby obtaining a ceramic-based composite high-temperature absorbing material.
[0018] Preferably, the components of the absorbing phase slurry include absorbing phase material, dispersant and solvent, the mass ratio of the absorbing phase material to the solvent is (1-7.5):1, and the added amount of the dispersant is 1-10% of the mass of the absorbing phase material.
[0019] Preferably, the injection pressure is 0.2-5 MPa; the drying temperature is 20-80° C., and the drying time is 1-8 h.
[0020] Preferably, the ceramic matrix precursor is polycarbosilane and / or polysilazane.
[0021] Preferably, the impregnation method is ultrasonic vacuum impregnation; the ultrasonic frequency of the ultrasonic vacuum impregnation is 40~120KHz, the vacuum degree is -1~-30kPa, and the impregnation time is 2~12h.
[0022] Preferably, the anaerobic thermal cracking is carried out in a nitrogen and / or argon atmosphere; the temperature of the anaerobic thermal cracking is 800-1200° C., and the time is 2-6 hours.
[0023] Preferably, the fiber preform with the absorbing phase dispersed therein is subjected to multiple cycles of impregnation and anaerobic pyrolysis until the weight gain of the product is ≤10%.
[0024] The present invention provides a ceramic-based composite high-temperature absorbing material as described in the above technical solution or a ceramic-based composite high-temperature absorbing material prepared by the preparation method as described in the above technical solution, and its application in heat-resistant protection, aerospace, radar absorption, stealth technology, electronic warfare or communication shielding.
[0025] Compared with the prior art, the present invention provides a ceramic-based composite high-temperature absorbing material and its preparation method and application. The components of the ceramic-based composite high-temperature absorbing material provided by the present invention include: a fiber preform, a multi-layer interface, an absorbing phase and a ceramic matrix; the fiber preform is a structural bearing member of the ceramic-based composite high-temperature absorbing material; the multi-layer interface is deposited on the surface of the fiber preform, including a PyC interface, a BN interface and a SiC interface; the absorbing phase is dispersed inside the fiber preform and is a bismuth layered structure ceramic phase, and the specific components are CaBi2Nb2O9, Bi3TiTaO9, Na 0.5 Bi 4.5 Ti4O 15or Bi3TiNbO9; the ceramic matrix is filled in the interior and surface of the fiber preform and the multilayer interface, and its composition is one or more of SiC, Si3N4 and SiCN. The ceramic-based composite high-temperature absorbing material provided by the present invention can maintain good absorbing performance at high temperatures, and has excellent mechanical properties and thermal stability, and has broad application prospects in the fields of heat-resistant protection, aerospace, radar absorbing, stealth technology, electronic warfare, communication shielding, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0027] Figure 1 1 is a graph showing the test results of the bending strength and wave absorbing performance of the composite material of Comparative Example 1 provided by the present invention;
[0028] Figure 2 This is a SEM image of the fracture microstructure of the composite material of Comparative Example 1 provided by the present invention;
[0029] Figure 3 is the XRD and dielectric thermogram of the composite material of Example 1 provided by the present invention;
[0030] Figure 4 is a graph showing the test results of the bending strength and wave absorbing performance of the composite material of Example 1 provided by the present invention;
[0031] Figure 5 is a graph showing the test results of the bending strength and wave absorbing performance of the composite material of Example 2 provided by the present invention;
[0032] Figure 6 It is a graph showing the test results of the bending strength and wave absorbing performance of the composite material of Example 3 provided by the present invention. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The invention provides a ceramic-based composite high-temperature wave-absorbing material, the components of which include: a fiber preform, a multilayer interface, a wave-absorbing phase and a ceramic matrix.
[0035] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the fiber preform is a structural bearing member, which mainly plays the role of enhancing the mechanical properties of the material, providing structural support, and promoting multiple scattering and energy absorption of electromagnetic waves.
[0036] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the fibers in the fiber preform are preferably one or more of carbon fibers, silica fibers, silicon carbide fibers, glass fibers, alumina fibers and zirconium oxide fibers, more preferably carbon fibers and silica fibers, and the volume ratio of the carbon fibers to the silica fibers is preferably 1: (1-4), more preferably 1:2.
[0037] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the weaving method of the fiber preform is preferably 2.5D acupuncture, three-dimensional orthogonal, fine weaving puncture or layer stitching; the bulk density of the fiber preform is preferably 0.4-0.7g / cm 3 , specifically 0.4g / cm 3 , 0.45g / cm 3 , 0.5g / cm 3 , 0.52g / cm 3 , 0.55g / cm 3 , 0.6g / cm 3 、0.63g / cm 3 , 0.65g / cm 3 or 0.7g / cm 3 ; The fiber volume fraction of the fiber preform is preferably 10-50 vol%, specifically 10 vol%, 15 vol%, 20 vol%, 25 vol%, 30 vol%, 35 vol%, 40 vol%, 45 vol% or 50 vol%; The thickness of the fiber preform is preferably 2-15 mm, specifically 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm.
[0038] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the fiber preform preferably accounts for 10-40% of the total volume of the ceramic composite material, specifically 10%, 12%, 15%, 17%, 20%, 23%, 25%, 27%, 30%, 32%, 35%, 37% or 40%.
[0039] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the multi-layer interface is deposited on the surface of the fiber preform, which mainly plays the role of improving interface matching, enhancing energy absorption and scattering, inhibiting reflected wave propagation, and improving thermal stability and anti-oxidation performance.
[0040] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the multilayer interface includes a pyrolytic carbon (PyC) interface, a boron nitride (BN) interface, and a silicon carbide (SiC) interface. In the present invention, the high-dielectric constant PyC interface is combined with the low-dielectric constant SiC and BN interfaces, which effectively optimizes the impedance matching of the material; the low-dielectric constant BN interface promotes electromagnetic waves to penetrate into the multilayer interface, enhancing dielectric losses such as interface polarization and dipole polarization; and the high-temperature resistant SiC and BN interface layers ensure the structural stability of the material in a high-temperature environment.
[0041] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the PyC interface in the multilayer interface is preferably deposited on the surface of the fiber preform, the BN interface in the multilayer interface is preferably deposited on the surface of the PyC interface, and the SiC interface in the multilayer interface is preferably deposited on the surface of the BN interface.
[0042] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the thickness of the PyC interface is preferably 100nm~1μm, specifically 100nm, 200nm, 250nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1μm; the thickness of the BN interface is preferably 100nm~1μm, specifically 100nm, 200nm, 250nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1μm; the thickness of the SiC interface is preferably 100nm~2μm, specifically 100nm, 200nm, 400nm, 500nm, 600nm, 800nm, 1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm or 2μm.
[0043] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the multilayer interface preferably accounts for 1-10% of the total volume of the ceramic composite material, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0044] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the absorbing phase is dispersed inside the fiber preform and is a bismuth-containing layered structure ceramic, which mainly plays the role of absorbing and converting electromagnetic wave energy, reducing reflectivity, enhancing the absorbing effect of the material in a specific frequency band, and improving the absorbing stability in a high-temperature environment.
[0045] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the components of the absorbing phase are specifically CaBi2Nb2O9, Bi3TiTaO9, Na 0.5 Bi 4.5 Ti4O 15or Bi3TiNbO9.
[0046] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the particle size of the absorbing phase is preferably ≤80 mesh, more preferably ≤100 mesh.
[0047] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the absorbing phase preferably accounts for 5-40% of the total volume of the ceramic composite material, specifically 5%, 7%, 10%, 12%, 15%, 17%, 20%, 23%, 25%, 27%, 30%, 32%, 35%, 37% or 40%.
[0048] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the ceramic matrix is filled in the interior of the fiber preform and the surface of the multilayer interface, and its components are one or more of SiC, Si3N4 and SiCN, which mainly plays the role of enhancing stability and oxidation resistance.
[0049] In the ceramic-based composite high-temperature absorbing material provided by the present invention, the ceramic matrix preferably accounts for 10-84% of the total volume of the ceramic composite material, specifically 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 84%.
[0050] The present invention also provides a method for preparing the ceramic-based composite high-temperature absorbing material of the above technical solution, comprising the following steps:
[0051] a) depositing a PyC interface, a BN interface and a SiC interface on the surface of the fiber preform to obtain a fiber preform having a multi-layer interface deposited thereon;
[0052] b) injecting a slurry of a microwave absorbing phase into the fiber preform on which the multi-layer interface is deposited, and drying and compacting the slurry to obtain a fiber preform with the microwave absorbing phase dispersed therein;
[0053] c) placing the fiber preform with the absorbing phase dispersed therein in a ceramic matrix precursor for impregnation, and after the impregnation is completed, taking out the fiber preform for anaerobic thermal cracking to crack the impregnated ceramic matrix precursor into a ceramic phase, thereby obtaining a ceramic-based composite high-temperature absorbing material.
[0054] In the preparation method provided by the present invention, in step a), the fibers in the fiber preform are preferably one or more of carbon fiber, silica fiber, silicon carbide fiber, glass fiber, alumina fiber and zirconium oxide fiber, more preferably carbon fiber and silica fiber, and the volume ratio of the carbon fiber to the silica fiber is preferably 1: (1-4), more preferably 1:2.
[0055] In the preparation method provided by the present invention, in step a), the weaving method of the fiber preform is preferably 2.5D acupuncture, three-dimensional orthogonal, fine weaving puncture or layer suture; the bulk density of the fiber preform is preferably 0.4-0.7 g / cm 3 , specifically 0.4g / cm 3 , 0.45g / cm 3 , 0.5g / cm 3 , 0.52g / cm 3 , 0.55g / cm 3 , 0.6g / cm 3 、0.63g / cm 3 , 0.65g / cm 3 or 0.7g / cm 3 ; The fiber volume fraction of the fiber preform is preferably 10-50 vol%, specifically 10 vol%, 15 vol%, 20 vol%, 25 vol%, 30 vol%, 35 vol%, 40 vol%, 45 vol% or 50 vol%; The thickness of the fiber preform is preferably 2-15 mm, specifically 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm.
[0056] In the preparation method provided by the present invention, in step a), the deposition method is preferably chemical vapor deposition (CVD) or chemical vapor infiltration (CVI).
[0057] In the preparation method provided by the present invention, in step a), the PyC interface, the BN interface and the SiC interface are preferably deposited layer by layer in sequence on the surface of the fiber preform.
[0058] In the preparation method provided by the present invention, in step a), the deposition of the PyC interface is preferably performed using methane (CH4) as a reaction gas; the deposition temperature of the PyC interface is preferably 1000-1100°C, specifically 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C or 1100°C; the deposition time of the PyC interface is preferably 20-50h, specifically 20h, 25h, 30h, 35h, 40h, 45h or 50h; the deposition thickness of the PyC interface is preferably 100nm-1μm, specifically 100nm, 200nm, 250nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1μm.
[0059] In the preparation method provided by the present invention, in step a), the deposition of the BN interface preferably uses boron trichloride (BCl3) and ammonia (NH3) as reaction gases, and hydrogen (H2) as carrier gas, and the mass flow ratio of BCl3, NH3 and H2 is preferably 1: (2-4): (8-12), more preferably 1:3:10; the deposition temperature of the BN interface is preferably 800°C-1000°C, specifically 800°C, 820°C, 850°C, 870°C, 900°C, 920°C, 950°C, 970°C or 1000°C; the deposition time of the BN interface is preferably 2-6h, specifically 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h; the deposition thickness of the BN interface is preferably 100nm~1μm, specifically 100nm, 200nm, 250nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1μm.
[0060] In the preparation method provided by the present invention, in step a), the deposition of the SiC interface preferably uses methyltrichlorosilane (CH3Cl3Si) as the reaction gas and hydrogen (H2) as the carrier gas, and the mass flow ratio of CH3Cl3Si to H2 is preferably 1:(8~12), more preferably 1:10; the deposition temperature of the SiC interface is preferably 1000~1200°C, specifically 1000°C, 1020°C, 1050°C, 1070°C, 1100°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, 1210°C, 1220°C, 1230°C, 1240°C, 1270°C, 1280°C, 1290°C, 1310°C, 1320°C, 1330°C, 1340°C, 1360°C, 1370°C, 1380°C, 1390°C, 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, 1460°C, 1470°C, 1480°C, 1490°C, 1500°C, 1510°C, 1520°C, 15 150°C, 1170°C or 1200°C; the deposition time of the SiC interface is preferably 0.5-12h, specifically 0.5h, 1h, 2h, 4h, 6h, 8h, 10h or 12h; the deposition thickness of the SiC interface is preferably 100nm-2μm, specifically 100nm, 200nm, 400nm, 500nm, 600nm, 800nm, 1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm or 2μm.
[0061] In the preparation method provided by the present invention, in step b), the components of the absorbing phase slurry preferably include absorbing phase materials, dispersants and solvents; wherein the absorbing phase materials are CaBi2Nb2O9, Bi3TiTaO9, Na 0.5 Bi 4.5 Ti4O 15or Bi3TiNbO9; the particle size of the absorbing phase material is preferably ≤80 mesh, more preferably ≤100 mesh; the dispersant is preferably polyvinyl pyrrolidone and / or triolein; the mass ratio of polyvinyl pyrrolidone to triolein is preferably 2:(0.5~2), more preferably 2:1; the amount of the dispersant added is preferably 1~10% of the mass of the absorbing phase material, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; the solvent is preferably ethanol; the mass ratio of the solvent to the absorbing phase material is preferably 1:(1~7.5), specifically 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:7.5. In the present invention, the absorbing phase slurry of the above-mentioned proportion of ingredients will neither be too thin to be lost through the preform during injection, nor too thick to be injected into the preform.
[0062] In the preparation method provided by the present invention, in step b), taking CaBi2Nb2O9 as an example of the absorbing phase material in the absorbing phase slurry, it is preferably prepared according to the following steps: CaCO3 powder, Bi2O3 powder and Nb2O5 powder are mixed according to a stoichiometric ratio, and CaBi2Nb2O9 ceramic powder is prepared by a solid phase sintering method. Among them, the molar ratio of the CaCO3 powder, Bi2O3 powder and Nb2O5 powder is preferably (1~0.1):(3~2):2; the heating rate of the solid phase sintering is preferably 1~10℃ / min, specifically 1℃ / min, 2℃ / min, 5℃ / min, 7℃ / min or 10℃ / min; the sintering temperature of the solid phase sintering is preferably 800~1200℃, specifically 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃ or 1200℃; the holding time of the solid phase sintering is preferably 2~8h, specifically 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0063] In the preparation method provided by the present invention, in step b), the absorbing phase slurry is preferably prepared according to the following steps: mixing the absorbing phase material, the dispersant and the solvent, ball milling, and removing bubbles to obtain the absorbing phase slurry. The rotation speed of the mixing ball mill is preferably 200-500 r / min, specifically 200 r / min, 300 r / min, 400 r / min or 500 r / min; the time of the mixing ball mill is preferably 4-8 h, specifically 4 h, 5 h, 6 h, 7 h or 8 h; the degassing method is preferably vacuum degassing.
[0064] In the preparation method provided by the present invention, in step b), the injection pressure of the absorbing phase slurry is preferably 0.2-5 MPa, specifically 0.2 MPa, 0.5 MPa, 1 MPa, 1.5 MPa, 2 MPa, 3 MPa, 4 MPa or 5 MPa.
[0065] In the preparation method provided by the present invention, in step b), the drying method after the injection of the absorbing phase slurry is preferably vacuum drying; the drying temperature is preferably 20-80°C, specifically 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C; the drying time is preferably 1-8h, specifically 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0066] In the preparation method provided by the present invention, in step c), the ceramic matrix precursor is preferably polycarbosilane (PCS) and / or polysilazane (PSN).
[0067] In the preparation method provided by the present invention, in step c), the impregnation method is preferably ultrasonic vacuum impregnation; the ultrasonic frequency of the ultrasonic vacuum impregnation is preferably 40-120KHz, specifically 40KHz, 50KHz, 60KHz, 70KHz, 80KHz, 90KHz, 100KHz, 110KHz or 120KHz; the vacuum degree of the ultrasonic vacuum impregnation is preferably -1-30kPa, specifically -1kPa, -5kPa, -10kPa, -15kPa, -20kPa, -25kPa or -30kPa; the impregnation time of the ultrasonic vacuum impregnation is preferably 2-12h, specifically 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h.
[0068] In the preparation method provided by the present invention, in step c), the anaerobic thermal cracking is preferably carried out in a nitrogen and / or argon atmosphere; the temperature of the anaerobic thermal cracking is preferably 800-1200°C, specifically 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C; the time of the anaerobic thermal cracking is preferably 2-6h, specifically 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h.
[0069] In the preparation method provided by the present invention, in step c), the fiber preform with the absorbing phase dispersed therein is preferably subjected to multiple cycles of repeated impregnation and anaerobic pyrolysis until the weight gain of the product is ≤10%; the number of repetitions is preferably 4 to 12 times, specifically 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times or 12 times.
[0070] In the preparation method provided by the present invention, in step c), the ceramic phase in the prepared ceramic-based composite high-temperature absorbing material is one or more of SiC, Si3N4 and SiCN.
[0071] The present invention also provides an application of the ceramic-based composite high-temperature absorbing material described in the above technical scheme or the ceramic-based composite high-temperature absorbing material prepared by the preparation method described in the above technical scheme in heat-resistant protection, aerospace, radar absorption, stealth technology, electronic warfare or communication shielding.
[0072] The technical solution provided by the present invention has at least the following beneficial effects:
[0073] (1) By simultaneously introducing multilayer interfaces and bismuth layered ceramic phases into ceramic matrix composites, the microwave absorption ability of the material under high temperature conditions is significantly improved, and it has a wider frequency response.
[0074] (2) The composite material provided by the present invention has light weight, good mechanical properties and high-temperature stability, and can meet the needs of high-performance materials in harsh environments.
[0075] (3) The composite material of the present invention can effectively improve the performance of high-temperature absorbing materials in the fields of aerospace, stealth technology, etc., and promote the advancement of related technologies.
[0076] For the purpose of greater clarity, the invention is described in detail through the following examples.
[0077] Comparative Example 1
[0078] This comparative example intends to prepare Cf@PyC / BN / SiC-SiCN ceramic-based composite material, which uses a carbon fiber (Cf) preform as a structural bearing member, and the surface of the Cf preform is deposited with PyC interface, BN interface and SiC interface layer by layer, and the interior and surface of the Cf preform and the multilayer interface are filled with SiCN as a ceramic matrix; wherein the Cf preform accounts for 32% of the total volume of the composite material, the multilayer interface (PyC / BN / SiC) accounts for 8% of the total volume of the composite material, and the SiCN matrix accounts for 60% of the total volume of the composite material.
[0079] The specific preparation process of the above ceramic matrix composite material is as follows:
[0080] Using T-700 continuous carbon fiber as raw material, a 2.5D needle punched preform was prepared with an initial density of 0.52 g / cm 3 , the volume fraction of carbon fiber in the preform is 30%, the thickness of the preform is 6 mm, the length is 60 mm, and the width is 60 mm;
[0081] The prepared fiber preform is placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C under continuous vacuum conditions, and then natural gas is introduced for deposition for 20 hours, and the thickness of the PyC interface on the prepared fiber surface is 250nm; then the preform with the PyC interface deposited is placed in a high-temperature vacuum sintering furnace again, the furnace temperature is raised to 900°C, boron trichloride, ammonia, and hydrogen are introduced into the furnace at a mass flow ratio of 1:3:10, and deposition is performed for 3 hours, and the thickness of the BN interface is 250nm; the preform with the PyC interface and BN interface deposited is once again placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C, methyltrichlorosilane and hydrogen are introduced into the furnace at a mass flow ratio of 1:10, and deposition is performed for 0.5 hours, and the thickness of the SiC interface is 500nm;
[0082] The carbon fiber preform with deposited multilayer interface was placed in polysilazane for ultrasonic vacuum impregnation treatment, wherein the impregnation time was 4 hours, the ultrasonic frequency was 120kHz, and the vacuum degree was -30kPa; the impregnated preform was placed in an atmosphere tube furnace, and was cracked at 900°C under a nitrogen protective atmosphere, and the pyrolysis time was 2 hours to remove organic matter in the organic precursor; this impregnation and cracking process was repeated 8 times to finally prepare the Cf@PyC / BN / SiC-SiCN ceramic-based composite material.
[0083] The density, flexural strength and wave absorption performance of the composite material sample prepared in Comparative Example 1 were tested. The results showed that the final density of the Cf@PyC / BN / SiC-SiCN composite material was 1.91 g / cm 3 ; The results of bending strength and wave absorption performance are as follows Figure 1 As shown, (a) is the bending strength, (b) is the absorbing performance, it can be seen that the room temperature bending strength of the composite material prepared in Comparative Example 1 is 449.4±71.0MPa, the minimum reflection loss value is -3.8dB, and the effective absorbing bandwidth is 0GHz; Figure 2 As shown, (a) and (b) are the SEM observation results of the fracture under different magnifications. It can be seen that obvious fiber pullout occurs at the fracture, and the fiber surface is smooth and complete without erosion damage, which is beneficial to the improvement of the mechanical properties of the material.
[0084] Example 1
[0085] In this study, we propose to prepare Cf@PyC / BN / SiC-SiCN (Ca 0.96 Bi 2.04 Nb2O9) ceramic-based composite high-temperature wave absorbing material, the material uses a carbon fiber (Cf) preform as a structural carrier, the surface of the Cf preform is deposited with PyC interface, BN interface and SiC interface layer by layer, and Ca is dispersed inside the Cf preform. 0.96 Bi2.04 Nb2O9 is used as the absorbing phase, and the interior and surface of the Cf preform and the multilayer interface are filled with SiCN as the ceramic matrix; among them, the Cf preform accounts for 32% of the total volume of the composite material, the multilayer interface (PyC / BN / SiC) accounts for 10% of the total volume of the composite material, and the Ca 0.96 Bi 2.04 The Nb2O9 absorbing phase accounts for 10% of the total volume of the composite material, and the SiCN matrix accounts for 50% of the total volume of the composite material.
[0086] The specific preparation process of the above ceramic-based composite high-temperature absorbing material is as follows:
[0087] Using T-700 continuous carbon fiber as raw material, a 2.5D needle-punched preform was prepared with an initial density of 0.52 g / cm 3 , the volume fraction of carbon fiber in the preform is 30%, the thickness of the preform is 6 mm, the length is 60 mm, and the width is 60 mm;
[0088] The prepared fiber preform is placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C under continuous vacuum conditions, and then natural gas is introduced for deposition for 20 hours, and the thickness of the PyC interface on the prepared fiber surface is 250nm; then the preform with the PyC interface deposited is placed in a high-temperature vacuum sintering furnace again, the furnace temperature is raised to 900°C, boron trichloride, ammonia, and hydrogen are introduced into the furnace at a mass flow ratio of 1:3:10, and deposition is performed for 3 hours, and the thickness of the BN interface is 250nm; the preform with the PyC interface and BN interface deposited is once again placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C, methyltrichlorosilane and hydrogen are introduced into the furnace at a mass flow ratio of 1:10, and deposition is performed for 0.5 hours, and the thickness of the SiC interface is 500nm;
[0089] 5.9 g of CaCO3, 19.7 g of Bi2O3, and 14.1 g of Nb2O5 powders were added to 24 g of anhydrous ethanol, and the suspension was poured out after ball milling at a speed of 300 r / min on a planetary ball mill for 4 h. After drying to remove the alcohol, the ceramic powder was ground and passed through a 100-mesh sieve, and then pressed into a 40×40×5 mm ceramic body; the ceramic body was placed in a muffle furnace and heated to 1100°C at a rate of 2°C / min for 2 h to complete sintering, and finally cooled with the furnace to obtain Ca 0.96 Bi 2.04 Nb2O9 ceramic sheet; grind the ceramic sheet into pieces and pass it through a 100-mesh sieve for later use;
[0090] 30g Ca 0.96 Bi 2.04Nb2O9 ceramic powder, 0.6g polyvinyl pyrrolidone, and 0.3g triolein were added to 15g anhydrous ethanol, and the suspension was poured out after ball milling at a speed of 300r / min for 6h on a planetary ball mill, and a uniform ceramic slurry was obtained after vacuum bubbling;
[0091] The uniformly dispersed Ca 0.96 Bi 2.04 The Nb2O9 ceramic slurry was uniformly injected into the carbon fiber preform with the multilayer interface deposited, and then vacuum dried at 60°C for 1h, and then compacted to obtain Ca 0.96 Bi 2.04 The carbon fiber toughened Ca 0.96 Bi 2.04 Nb2O9 ceramic green body;
[0092] The ceramic green body was placed in polysilazane for ultrasonic vacuum impregnation treatment, wherein the impregnation time was 4 hours, the ultrasonic frequency was 120kHz, and the vacuum degree was -30kPa; after impregnation, the ceramic green body was placed in an atmosphere tube furnace, and pyrolysis treatment was performed at 900°C under a nitrogen protective atmosphere for 2 hours to remove organic matter in the organic precursor; this impregnation pyrolysis process was repeated 8 times, and finally Cf@PyC / BN / SiC-SiCN(Ca 0.96 Bi 2.04 Nb2O9) ceramic-based composite high-temperature absorbing material.
[0093] The composite material prepared in Example 1 was subjected to XRD phase analysis and dielectric temperature spectrum analysis. The results are as follows: Figure 3 As shown in the figure, (a) is the XRD spectrum, and (b) is the dielectric temperature spectrum. It can be seen that the ceramic phase is mainly composed of Ca 0.96 Bi 2.04 Nb2O9, and the Curie temperature of the ceramic can reach 934°C. At the same time, the density, bending strength and wave absorption performance of the composite material sample prepared in Example 1 were tested. The results showed that: Cf@PyC / BN / SiC-SiCN (Ca 0.96 Bi 2.04 The final density of the composite material is 2.3 g / cm 3 ; The results of bending strength and wave absorption performance are as follows Figure 4 As shown, (a) is the bending strength, and (b) is the absorbing performance. It can be seen that the room temperature bending strength of the composite material prepared in Example 1 is 336.6±36.6MPa, the minimum reflection loss value is -19.9dB, and the effective absorbing bandwidth is 2.94GHz.
[0094] Example 2
[0095] This paper proposes to prepare Cf / SiO2f@PyC / BN / SiC-SiCN (Ca 0.96 Bi 2.04 Nb2O9) ceramic-based composite high-temperature wave absorbing material, which uses carbon fiber (Cf) and silicon dioxide fiber (SiO2f) preforms as structural bearing parts, and the surface of the preform is deposited with PyC interface, BN interface and SiC interface layer by layer, and Ca is dispersed inside the preform. 0.96 Bi 2.04 Nb2O9 is used as the absorbing phase, and the interior and surface of the preform and the multilayer interface are filled with SiCN as the ceramic matrix; among them, the Cf / SiO2f preform accounts for 32% of the total volume of the composite material, the multilayer interface (PyC / BN / SiC) accounts for 8% of the total volume of the composite material, and the Ca 0.96 Bi 2.04 The Nb2O9 absorbing phase accounts for 10% of the total volume of the composite material, and the SiCN matrix accounts for 50% of the total volume of the composite material.
[0096] The specific preparation process of the above ceramic-based composite high-temperature absorbing material is as follows:
[0097] Carbon fiber cloth and silica fiber cloth were used as raw materials. The volume ratio of carbon fiber cloth to silica fiber cloth was 1:2. A 2.5D needle-punched preform was prepared. The initial density of the preform was 0.45 g / cm 3 , the fiber volume fraction in the preform is 30%, the preform thickness is 6 mm, the length is 60 mm, and the width is 60 mm;
[0098] The prepared fiber preform is placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C under continuous vacuum conditions, and then natural gas is introduced for deposition for 20 hours, and the thickness of the PyC interface on the prepared fiber surface is 250nm; then the preform with the PyC interface deposited is placed in a high-temperature vacuum sintering furnace again, the furnace temperature is raised to 900°C, boron trichloride, ammonia, and hydrogen are introduced into the furnace at a mass flow ratio of 1:3:10, and deposition is performed for 3 hours, and the thickness of the BN interface is 250nm; the preform with the PyC interface and BN interface deposited is once again placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C, methyltrichlorosilane and hydrogen are introduced into the furnace at a mass flow ratio of 1:10, and deposition is performed for 0.5 hours, and the thickness of the SiC interface is 500nm;
[0099] 5.9 g of CaCO3, 19.7 g of Bi2O3, and 14.1 g of Nb2O5 powders were added to 24 g of anhydrous ethanol, and the suspension was poured out after ball milling at a speed of 300 r / min on a planetary ball mill for 4 h. After drying to remove the alcohol, the ceramic powder was ground and passed through a 100-mesh sieve, and then pressed into a 40×40×5 mm ceramic body; the ceramic body was placed in a muffle furnace and heated to 1100°C at a rate of 2°C / min for 2 h to complete sintering, and finally cooled with the furnace to obtain Ca 0.96 Bi 2.04 Nb2O9 ceramic sheet; grind the ceramic sheet into pieces and pass it through a 100-mesh sieve for later use;
[0100] 30g Ca 0.96 Bi 2.04 Nb2O9 ceramic powder, 0.6g polyvinyl pyrrolidone, and 0.3g triolein were added to 15g anhydrous ethanol, and the suspension was poured out after ball milling at a speed of 300r / min for 6h on a planetary ball mill, and a uniform ceramic slurry was obtained after vacuum bubbling;
[0101] The uniformly dispersed Ca 0.96 Bi 2.04 The Nb2O9 ceramic slurry was uniformly injected into the mixed fiber preform, and then vacuum dried at 60°C for 1 h, and then compacted to obtain Ca 0.96 Bi 2.04 The Nb2O9 ceramic material is uniformly filled in the pores of the hybrid fiber preform. 0.96 Bi 2.04 Nb2O9 ceramic green body;
[0102] The ceramic green body was placed in polysilazane for ultrasonic vacuum impregnation treatment, wherein the impregnation time was 4 hours, the ultrasonic frequency was 120kHz, and the vacuum degree was -30kPa; after impregnation, the ceramic green body was placed in an atmosphere tube furnace, and was cracked at 900°C under a nitrogen protective atmosphere for 2 hours to remove organic matter in the organic precursor; this impregnation and cracking process was repeated 8 times, and finally Cf / SiO2f@PyC / BN / SiC-SiCN(Ca 0.96 Bi 2.04 Nb2O9) ceramic-based composite high-temperature absorbing material.
[0103] The density, bending strength and wave absorption performance of the composite material sample prepared in Example 2 were tested. The results showed that: Cf / SiO2f@PyC / BN / SiC-SiCN (Ca 0.96 Bi 2.04 The final density of the composite material is 2.4 g / cm 3; The results of bending strength and wave absorption performance are as follows Figure 5 As shown, (a) is the bending strength, and (b) is the absorbing performance. It can be seen that the room temperature bending strength of the composite material prepared in Example 2 is at least 284.4±29.3 MPa, the minimum reflection loss value is -31.1 dB, and the effective absorbing bandwidth is 5.06 GHz.
[0104] Example 3
[0105] This paper proposes to prepare Cf / SiO2f@PyC / BN / SiC-SiCN (Ca 0.96 Bi 2.04 Nb2O9) ceramic-based composite high-temperature wave absorbing material, which uses carbon fiber (Cf) and silicon dioxide fiber (SiO2f) preforms as structural bearing parts, and the surface of the preform is deposited with PyC interface, BN interface and SiC interface layer by layer, and Ca is dispersed inside the preform. 0.96 Bi 2.04 Nb2O9 is used as the absorbing phase, and the interior and surface of the preform and the multilayer interface are filled with SiCN as the ceramic matrix; among them, the Cf / SiO2f preform accounts for 32% of the total volume of the composite material, the multilayer interface (PyC / BN / SiC) accounts for 8% of the total volume of the composite material, and the Ca 0.96 Bi 2.04 The Nb2O9 absorbing phase accounts for 10% of the total volume of the composite material, and the SiCN matrix accounts for 50% of the total volume of the composite material.
[0106] The specific preparation process of the above ceramic-based composite high-temperature absorbing material is as follows:
[0107] Carbon fiber cloth and silica fiber cloth were used as raw materials. The volume ratio of carbon fiber cloth to silica fiber cloth was 1:2. A laminated stitched preform was prepared. The initial density of the preform was 0.63 g / cm 3 The fiber volume fraction in the preform is 45%, the preform thickness is 6 mm, the length is 60 mm, and the width is 60 mm.
[0108] The prepared fiber preform is placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C under continuous vacuum conditions, and then natural gas is introduced for deposition for 20 hours, and the thickness of the PyC interface on the prepared fiber surface is 250nm; then the preform with the PyC interface deposited is placed in a high-temperature vacuum sintering furnace again, the furnace temperature is raised to 900°C, boron trichloride, ammonia, and hydrogen are introduced into the furnace at a mass flow rate ratio of 1:3:10, and deposition is performed for 3 hours, and the thickness of the BN interface is 250nm; the preform with the PyC interface and BN interface deposited is once again placed in a high-temperature vacuum sintering furnace, the furnace temperature is raised to 1100°C, methyltrichlorosilane and hydrogen are introduced into the furnace at a ratio of 1:10, and deposition is performed for 0.5 hours, and the thickness of the SiC interface is 500nm;
[0109] 5.9 g of CaCO3, 19.7 g of Bi2O3, and 14.1 g of Nb2O5 powders were added to 24 g of anhydrous ethanol, and the suspension was poured out after ball milling at a speed of 300 r / min on a planetary ball mill for 4 h. After drying to remove the alcohol, the ceramic powder was ground and passed through a 100-mesh sieve, and then pressed into a 40×40×5 mm ceramic body; the ceramic body was placed in a muffle furnace and heated to 1100°C at a rate of 2°C / min for 2 h to complete sintering, and finally cooled with the furnace to obtain Ca 0.96 Bi 2.04 Nb2O9 ceramic sheet; grind the ceramic sheet into pieces and pass it through a 100-mesh sieve for later use;
[0110] 30g Ca 0.96 Bi 2.04 Nb2O9 ceramic powder, 0.6g polyvinyl pyrrolidone, and 0.3g triolein were added to 15g anhydrous ethanol, and the suspension was poured out after ball milling at a speed of 300r / min for 6h on a planetary ball mill, and a uniform ceramic slurry was obtained after vacuum bubbling;
[0111] The uniformly dispersed Ca 0.96 Bi 2.04 The Nb2O9 ceramic slurry was uniformly injected into the mixed fiber preform, and then vacuum dried at 60°C for 1 h, and then compacted to obtain Ca 0.96 Bi 2.04 The Nb2O9 ceramic material is uniformly filled in the pores of the hybrid fiber preform. 0.96 Bi 2.04 Nb2O9 ceramic green body;
[0112] The ceramic green body was placed in polysilazane for ultrasonic vacuum impregnation treatment, wherein the impregnation time was 4 hours, the ultrasonic frequency was 120kHz, and the vacuum degree was -30kPa; after impregnation, the ceramic green body was placed in an atmosphere tube furnace, and was cracked at 900°C under a nitrogen protective atmosphere for 2 hours to remove organic matter in the organic precursor; this impregnation and cracking process was repeated 8 times, and finally Cf / SiO2f@PyC / BN / SiC-SiCN(Ca 0.96 Bi 2.04 Nb2O9) ceramic-based composite high-temperature absorbing material.
[0113] The density, bending strength and wave absorption performance of the composite material samples prepared in Example 3 were tested. The results showed that: 0.96 Bi 2.04The final density of the composite material is 2.4 g / cm 3 ; The results of bending strength and wave absorption performance are as follows Figure 6 As shown, (a) is the bending strength, and (b) is the absorbing performance. It can be seen that the room temperature bending strength of the composite material prepared in Example 3 is at least 276.4±16.9 MPa, the minimum reflection loss value is -25 dB, and the effective absorbing bandwidth is 5.3 GHz.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A ceramic-based composite high-temperature absorbing material, characterized in that: The components of the ceramic-based composite high-temperature absorbing material include: a fiber preform, a multilayer interface, an absorbing phase and a ceramic matrix; The fiber preform is a structural bearing member of the ceramic-based composite high-temperature absorbing material; The multilayer interface is deposited on the surface of the fiber preform, including a PyC interface, a BN interface and a SiC interface; The absorbing phase is dispersed inside the fiber preform and is a bismuth layered structure ceramic phase, and the specific composition is CaBi2Nb2O9, Bi3TiTaO9, Na 0.5 Bi 4.5 Ti4O 15 or Bi3TiNbO9; The ceramic matrix is filled in the interior of the fiber preform and the surface of the multilayer interface, and its composition is one or more of SiC, Si3N4 and SiCN.
2. The ceramic-based composite high-temperature absorbing material according to claim 1, characterized in that: The fibers in the fiber preform are one or more of carbon fibers, silicon dioxide fibers, silicon carbide fibers, glass fibers, aluminum oxide fibers and zirconium oxide fibers.
3. The ceramic-based composite high-temperature absorbing material according to claim 1, characterized in that: The fiber preform is woven in a manner of 2.5D acupuncture, three-dimensional orthogonal, fine-weave puncture or layer stitching, and has a body density of 0.4-0.7 g / cm 3 The fiber volume fraction is 10~50vol% and the thickness is 2~15mm.
4. The ceramic-based composite high-temperature absorbing material according to claim 1, characterized in that: The PyC interface is deposited on the surface of the fiber preform, the BN interface is deposited on the surface of the PyC interface, and the SiC interface is deposited on the surface of the BN interface.
5. The ceramic-based composite high-temperature absorbing material according to claim 1, characterized in that: The thickness of the PyC interface is 100 nm to 1 μm; the thickness of the BN interface is 100 nm to 1 μm; and the thickness of the SiC interface is 100 nm to 2 μm.
6. A method for preparing the ceramic-based composite high-temperature absorbing material according to any one of claims 1 to 5, characterized in that: The following steps are involved: a) depositing a PyC interface, a BN interface and a SiC interface on the surface of the fiber preform to obtain a fiber preform having a multi-layer interface deposited thereon; b) injecting a slurry of a microwave absorbing phase into the fiber preform on which the multi-layer interface is deposited, and drying and compacting the slurry to obtain a fiber preform with the microwave absorbing phase dispersed therein; c) placing the fiber preform with the absorbing phase dispersed therein in a ceramic matrix precursor for impregnation, and after the impregnation is completed, taking out the fiber preform for anaerobic thermal cracking to crack the impregnated ceramic matrix precursor into a ceramic phase, thereby obtaining a ceramic-based composite high-temperature absorbing material.
7. The preparation method according to claim 6, characterized in that: The components of the absorbing phase slurry include absorbing phase material, dispersant and solvent. The mass ratio of the absorbing phase material to the solvent is (1-7.5):1, and the added amount of the dispersant is 1-10% of the mass of the absorbing phase material.
8. The preparation method according to claim 6, characterized in that: The injection pressure is 0.2-5 MPa; the drying temperature is 20-80° C., and the drying time is 1-8 hours.
9. The preparation method according to claim 6, characterized in that: The ceramic matrix precursor is polycarbosilane and / or polysilazane; The impregnation method is ultrasonic vacuum impregnation; the ultrasonic frequency of the ultrasonic vacuum impregnation is 40~120KHz, the vacuum degree is -1~-30kPa, and the impregnation time is 2~12h; The anaerobic thermal cracking is carried out in a nitrogen and / or argon atmosphere; the temperature of the anaerobic thermal cracking is 800-1200° C., and the time is 2-6 hours; The fiber preform with the absorbing phase dispersed therein is subjected to multiple cycles of impregnation and anaerobic pyrolysis until the weight gain of the product is ≤10%.
10. Use of the ceramic-based composite high-temperature absorbing material according to any one of claims 1 to 5 or the ceramic-based composite high-temperature absorbing material obtained by the preparation method according to any one of claims 6 to 9 in heat-resistant protection, aerospace, radar absorbing, stealth technology, electronic warfare or communication shielding.
Citation Information
Patent Citations
Multiferroic wave absorbing material and preparation method thereof
CN110922180A
High-temperature-resistant wave-absorbing structure integrated ceramic matrix composite material and preparation method thereof
CN112876273A